Mergers and Acquisition: An Analytical Study of the Benefits and Set-backs - Narnolia, Piyush (International Journal of Recent Advances in Multidisciplinary Topics, 2023)
Mergers and acquisitions have long been the favoured approach for companies seeking inorganic growth. They are commonly used to restructure corporate setups and pursued for strategic business reasons that are primarily financial in nature. This study aims to evaluate the impact of acquiring firms’ past and subsequent financial performance. The employment of mergers and acquisitions (M&As) has witnessed a global increase, allowing companies to expand their size and/or market share, diversify product offerings, mitigate business and financial risks, enter new markets, achieve economies of scale, and pursue various other objectives. While speculation and optimism surround mergers, and research has been conducted on how the stock market responds to such announcements, it is essential to assess whether joining forces with businesses in the same or different industries will genuinely enhance financial operating performance. Only then can such merger activities be justified. The effects of mergers and acquisitions can be both advantageous and detrimental, making it imperative to conduct comprehensive research on the subject and thoroughly examine the outcomes.